Analysis of elasticity of several kinds of eggs demand in North Tapanuli Regency - Susiana Nababan; Sayed Umar; Iskandar Sembiring; Hamdan .; Nevy Diana Hanafi (Jurnal Peternakan Integratif, 2017)
ABSTRACT. This study aims to determine the effect of price level on egg demand  and to analyze factors affecting egg demand price in North Tapanuli regency. In addition, this study also to investigate how big the elasticity of egg demand  and to know marketing channel eggs in North Tapanuli Regency. This research use survey method with consumer respondent unit and egg consumer. The sample was obtained by accidental sampling method and obtained 48 traders and 90 consumers. Data analysis was done descriptively and statistically. The results showed that the ras chicken egg and buras chicken egg are elastic while the duck eggs are inelastic. The demand for ras chicken eggs is significantly influenced by the number of dependents and substitute goods (tofu). Demand for duck eggs and buras chicken eggs is significantly influenced by the number of dependents. The more the number of family dependents then the number of egg demand will be higher. Influence of a good from the price of other goods because each item has a mutual relationship replace the function of usability, and also complement each other.